2019
DOI: 10.1108/bpmj-11-2017-0299
|View full text |Cite
|
Sign up to set email alerts
|

Process improvement capability: a study of the development of practice(s)

Abstract: Purpose The purpose of this paper is to report on a research project, using intervention research (IR), which aims to identify how a higher education institution could develop process improvement (PI) capability. Design/methodology/approach The paper adopts a practice perspectives of routines, and classifies and catalogues the potential routines that could form PI capability. The development of these routines are investigated using the constructive research approach, a form of IR), in the action research mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 118 publications
0
4
0
Order By: Relevance
“…More importantly, the reference framework (refer to Figure 5) provides three main functions, along with 20 subfunctions, which can be used systematically by firms considering the multiple-level groups. Moreover, if the results are compared with other studies and the difference is described, some of the parts in Figure 5 remain true to previous studies concluded: (1) closeout claims [26]; (2) improvement of organisational ambidexterity [31][32][33]72,73]; (3) dispute settlement [23,77,79,81]; (4) claim phases and timeline [9,61,62]; (5) CMO maturity level [21]; (6) claim performance indicators [22,58]. However, as previous scholars have reported on OPM-related decisions [17,19,20], past research has not figured out how all of these behavioural-based concepts can be integrated into the design structure of CMO in firms' organisations.…”
Section: Discussion and Contributionsmentioning
confidence: 56%
See 1 more Smart Citation
“…More importantly, the reference framework (refer to Figure 5) provides three main functions, along with 20 subfunctions, which can be used systematically by firms considering the multiple-level groups. Moreover, if the results are compared with other studies and the difference is described, some of the parts in Figure 5 remain true to previous studies concluded: (1) closeout claims [26]; (2) improvement of organisational ambidexterity [31][32][33]72,73]; (3) dispute settlement [23,77,79,81]; (4) claim phases and timeline [9,61,62]; (5) CMO maturity level [21]; (6) claim performance indicators [22,58]. However, as previous scholars have reported on OPM-related decisions [17,19,20], past research has not figured out how all of these behavioural-based concepts can be integrated into the design structure of CMO in firms' organisations.…”
Section: Discussion and Contributionsmentioning
confidence: 56%
“…(1) considering the rejected requests of project issue management-Shalwani and Lines [25] proffer that issue management (as a project control technique) as a solution for mitigating project challenges by using the issue log during execution for the remainder of the project; and (2) considering organisational project/program management [70,71]. In addition, some scholars [72,73] claim that process improvement of organisational ambidexterity is critical to understanding its conflicting aims and contradictory variations. 'Ambidextrous program management' (as a new type of multi-project management) bridges the project management and ambidexterity literature [30].…”
Section: Theories Foundations Of Cmo Within Project-based Organisationsmentioning
confidence: 99%
“…This would consist of an assemblage of performance management practices a priori to an implementation of a fully-fledged PMS system, but with the explicit goal of productivity improvement. Jones et al (2019) refer to this type of inaugural assemblage as 'initialising practices'.…”
Section: Introductionmentioning
confidence: 99%
“…The working code of gathering process data best fits Biazzo's ( 2002) term of 'process analysis', which is about collecting and investigating information about the process. Jones et al (2019) introduces the idea of working with a process map, which 'sits' between defining and mapping a process, and adherence to a process. It is about revising and correcting a process map with key actors, as well as talking about the process, utilising the process map artefact.…”
mentioning
confidence: 99%